2002
DOI: 10.1097/00002030-200207050-00009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of early initiation of HAART in patients with asymptomatic HIV infection and CD4 cell count > 350 × 106/l

Abstract: The initiation of HAART in asymptomatic patients with CD4 cell count > 350 x 10(6)/l significantly delayed clinical progression. However, the risk of severe clinical events with deferred therapy was low and must be counter balanced against the burden and toxicity of HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 44 publications
2
44
1
1
Order By: Relevance
“…Opravil et al [27] reported that individuals who initiated ART with !350 CD4 T cells/mL experienced significantly more CDC category B or C events than did patients who initiated ART with higher CD4 T cell counts. In the present study, 22 (21.0%) of 105 incomplete responders had clinical CDC category B or C events; for 15 (68%), the events were opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Opravil et al [27] reported that individuals who initiated ART with !350 CD4 T cells/mL experienced significantly more CDC category B or C events than did patients who initiated ART with higher CD4 T cell counts. In the present study, 22 (21.0%) of 105 incomplete responders had clinical CDC category B or C events; for 15 (68%), the events were opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests a reduction in death, opportunistic infections, and serious non-AIDS events and an increase in rates of maximal virologic suppression and CD4 cell counts in patients who initiate therapy with CD4 counts between 200 to 350 cells/l (5,10,16,20,29,30,38,43,49,53,57,67). Data from a large observational cohort recently demonstrated an increased risk of death in patients who did not initiate antiretroviral therapy with CD4 counts either between 351 to 500 cells/l or of Ͼ500 cells/l relative to patients in those CD4 strata that did initiate therapy (26).…”
Section: When To Start Therapy?mentioning
confidence: 99%
“…There is consensus that therapy should be initiated when a patient develops an opportunistic infection or has CD4 cell count < 200 [23]. Above this, there is a debate over the optimal starting CD4 cell count [24][25][26]. Data indicates a much higher morbidity and mortality rate if started at CD4 < 200.…”
Section: Key Principles and Complexities Of Antiretroviral Therapymentioning
confidence: 99%